Social Impacts of Child Marriage in Grobogan Regency, Central Java Province, Indonesia (Medico Legal Update, 2020)
Background: The prevalence of child marriage in Indonesia has more than doubled in the last three decadesbut is still one of the highest in the East Asia and Pacific region. In the Grobogan District in 2016 anincrease in the number of marriages at an early age in women was 36.5 percent. This study is a qualitativenaturalistic study. The main data source of this study is the results of Focus Group Discussions, interviewsand observations and also supported by secondary data in the form of previous research results. The reasonfor early marriage is mostly due to the incidence of pregnancy outside marriage in adolescents. It is suspectedthat there is a relationship between early marriage, low level of education and poverty. Religious education,morals and strict control from parents, schools and communities must be done with a variety of strategies,because most of the reasons for early marriage are getting pregnant first.